Early activation of bioenergetic metabolism powers bacterial spore germination - Pooja Gupta; Rebecca Caldbeck; Rowan C. Walters; Elodie C. Wells; Bethany L. Hardman; Graham Christie; Roger J. Springett; James N. Blaza (Proceedings of the National Academy of Sciences, 2025)
Dormant bacterial spores germinate to become vegetative cells upon germinant exposure. Despite many germinants being energy sources, bioenergetic processes have been overlooked as germination can proceed, albeit slowly, without exogenous energy sources. Here, we apply remission spectroscopy to noninvasively measure energization of the electron transport chain (ETC) in germinating spores. In Bacillus megaterium and Bacillus subtilis , energization of cytoplasmic metabolism and the ETC occurs early in germination, before or alongside water ingress and bulk CaDPA efflux. The aa 3 -type oxidases (Qox, Cta) accumulate nonradical ferryl intermediates of their catalytic cycle, slowed by a high membrane potential. The Yth isoform of the bd oxidase, present in spores, allows rapid electron transfer to O 2 when the aa 3 -type oxidases are hindered, establishing a role for this enzyme. Deletion of Yth slows the initiation of “absorbance”/attenuance loss, directly linking bioenergetic processes to germination. We propose a powered germination model, where the Ger-mediated signaling cascade and bioenergetic processes occur in parallel and are mutually influenced by each other. This model explains why germination on energy-rich molecules (e.g., glucose) is often much faster than on energy-poor ones (e.g., KBr).